Constitutional Privileges and Criminal Law: Resocialization of Natives in Prison - Benítez Núñez, Christian; Noriega Villamizar, Angélica Patricia; Abarca, Ulises Patricio (DIXI, 2017)
Theme and scope: This article approaches the current state of resocialization with regard to convicted natives in state prisons, as well as the contents and meaning that should guide the purpose of punishment. Moreover, the scope of indigenous jurisdictional power is addressed, which has been widely discussed in writings of jurists and the case law on how to overcome the dichotomy of the discourse between the protection of fundamental liberal rights and the preservation and conservation of native peoples to prevent their subsequent disappearance. Characteristics: Specifying that this tension occurs due to the customs and worldview of indigenous peoples compared to Western customs. Findings: The criminal law in charge of punishing behaviors that have the characteristics of a crime has pro- vided a whole theory about the purposes of punishment that has been somehow adopted by indigenous communities as a solution to conflicts. Conclusions: The importance of providing the concept of ethnically differentiated resocialization with contents is advised since this can lead to constructing an appropriate theory that allows imprisoned natives to have an adequate treatment plan and to deal with the structural differences this entails.